2022
DOI: 10.1093/geroni/igac059.2580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dance Interventions on Cognition in Older Adults: A Meta-Analysis

Abstract: Background Dance interventions have been shown to improve cognition in older adults. However, no meta-analysis evaluates that effect. Objective: We examined the effects of dance on cognition in older adults and examined the moderating effects of participant, methods, and intervention characteristics. Methods We searched 14 databases using the search terms: dance AND cognition AND older adults. Researchers of primary studies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Research has demonstrated that reminiscence therapy that utilises music familiar with past experiences can be a powerful delivery method (Cuevas et al, 2020). Rittiwong et al (2023) suggest that dance tailored to older adults' cultural backgrounds may promote enjoyment and alleviate depression. From a phenomenological point of view, past experiences are physically stored in the body, and dance has been suggested as a way to elicit memories during reminiscence therapy (Klever, 2013; Skinner, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that reminiscence therapy that utilises music familiar with past experiences can be a powerful delivery method (Cuevas et al, 2020). Rittiwong et al (2023) suggest that dance tailored to older adults' cultural backgrounds may promote enjoyment and alleviate depression. From a phenomenological point of view, past experiences are physically stored in the body, and dance has been suggested as a way to elicit memories during reminiscence therapy (Klever, 2013; Skinner, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…53 In older adults, dance was helpful in improving depressive symptoms. 54 A network meta-analysis comparing exercise and pharmacotherapy for nonsevere depression found that exercise had a higher dropout rate than pharmacotherapy, but was equally effective in reducing depressive symptoms. 55 Physical activity is beneficial in the prevention and treatment of depression.…”
Section: Exercise Therapy and Physical Activitymentioning
confidence: 99%
“…Tai chi was useful in improving depression, anxiety, and general mental health 53 . In older adults, dance was helpful in improving depressive symptoms 54 . A network meta‐analysis comparing exercise and pharmacotherapy for non‐severe depression found that exercise had a higher dropout rate than pharmacotherapy, but was equally effective in reducing depressive symptoms 55 …”
Section: Rehabilitation Nutrition For Depressionmentioning
confidence: 99%